2016
DOI: 10.1038/srep24580
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Inhibition Blocks Palmitic Acid-induced inflammation in cardiomyocytes and Prevents Hyperlipidemia-induced Cardiac Injury in Mice

Abstract: Obesity is often associated with increased risk of cardiovascular diseases. Previous studies suggest that epidermal growth factor receptor (EGFR) antagonism may be effective for the treatment of angiotensin II-induced cardiac hypertrophy and diabetic cardiomyopathy. This study was performed to demonstrate if EGFR plays a role in the pathogenesis of hyperlipidemia/obesity-related cardiac injuries. The in vivo studies using both wild type (WT) and apolipoprotein E (ApoE) knockout mice fed with high fat diet (HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…In addition, expression of TLR4-induced genes in lipopolysaccharide-stimulated myeloid cells requires EGFR kinase activity18. We have also found that TLR4 and c-Src mediate palmitic acid-induced EGFR activation in cardiomyocyte-like H9c2 cells34. Thus, we tested whether TLR4/c-Src mediates ox-LDL-induced EGFR activation in macrophages.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, expression of TLR4-induced genes in lipopolysaccharide-stimulated myeloid cells requires EGFR kinase activity18. We have also found that TLR4 and c-Src mediate palmitic acid-induced EGFR activation in cardiomyocyte-like H9c2 cells34. Thus, we tested whether TLR4/c-Src mediates ox-LDL-induced EGFR activation in macrophages.…”
Section: Resultsmentioning
confidence: 94%
“…Li et al (2016) found that EGFR inhibitors reduce myocardial inflammation, fibrosis, apoptosis and dysfunction in two murine obesity models, together with inhibiting palmitate-dependent inflammation and apoptosis in H9c2 cells. This is consistent with saturated fatty acid inhibition of NRG1b activation of myocyte PI3K/Akt signalling, an effect countered by a monounsaturated fatty acid (oleate) (Miller et al, 2009).…”
Section: Obesity/dyslipidemiamentioning
confidence: 95%
“…Over-activity of EGFR in diabetes/metabolic disorders, for example, may exaggerate inflammation and oxidative stress in cardiac Li et al, 2016) and other tissues (Fang et al, 2016). Inhibitors of EGFR have also been shown to reduce insulin-resistance (Prada et al, 2009), atherosclerosis and vascular dysfunction in (Choi et al, 2012) in models of obesity, dyslipidemia and diabetes.…”
Section: Understanding Complexities In Egfr Modulationmentioning
confidence: 99%
“…The molecular components of the TLR4 receptor complex formed in response to FnIII domains are not well understood. Based on recent findings linking TLR4 to epidermal growth factor receptor (EGFR)/ Src signaling, [26][27][28] we evaluated whether either EGFR or Src kinases contributed to IL-8 release initiated by FnEDA and FnIII-1c. As shown in Fig.…”
mentioning
confidence: 99%